2017
DOI: 10.1016/j.ijscr.2017.07.065
|View full text |Cite
|
Sign up to set email alerts
|

Primary Ewing’s sarcoma of the kidney: A case report

Abstract: This is a 15-year-old female who presented with sudden onset left flank pain associated with nausea and vomiting and a history of weight loss. Radiological investigation revealed a large non-obstructive tumor involving the lower pole of the left kidney which was primarily thought to be a renal cell carcinoma. She underwent left open radical nephrectomy with adrenalectomy. Histopathology of the resected specimen showed features of Ewing’s sarcoma of the kidney which was confirmed by cytogenetic analysis. This i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
3
0
1
Order By: Relevance
“…There is no established standard of treatment for renal EWS because of its scarcity. The management of EWS typically encompasses surgical resection, coupled with adjuvant chemotherapy, with or without neoadjuvant chemotherapy, and radiotherapy [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no established standard of treatment for renal EWS because of its scarcity. The management of EWS typically encompasses surgical resection, coupled with adjuvant chemotherapy, with or without neoadjuvant chemotherapy, and radiotherapy [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…It occurs mostly in bones, while extraskeletal sites account for ~20%–30% of the cases [ 2 ]. Renal extraskeletal EWS is extremely rare, with 48 cases reported in the English literature to date [ 3 ]. It represents <1% of all renal tumours [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Khaliq et al in 201215 reported a case of a 52-year-old healthy woman who presented with a 2-week history of pain in her right posterior thigh that was not relieved by non-steroidal anti-inflammatory medicine and physical therapy. Alasmari et al 16 describes primary Ewing’s sarcoma of kidney in a 15-year-old female patient and Adisesh et al 17 describes a case of 19-year-old young man reported with pain and mild swelling of the upper end of right tibia.…”
Section: Discussionmentioning
confidence: 99%
“…Das Ewing-Sarkom und der primitive neuroektodermale Tumor (PNET) sind neuroektodermale Neoplasien, welche aufgrund ihrer histopathologischen und zytogenetischen Ähnlichkeiten dem Spektrum der Ewing-Sarkom-Familie zugeordnet werden (Almeida et al 2014). Spezifisch für diese Tumore ist die Bildung des chimären EWS-FLI-1-Gens (ein Onkogen) durch eine Translokation zwischen den Chromosomen 22 und 11 (Alasmari et al 2017). Auch phänotypisch sind die beiden Entitäten eng miteinander verwandt.…”
Section: Histologische Klassifikationunclassified